Оn the Issue of Effective Allocation of Investments in RA - Karapetyan, Liana (Journal of Sociology: Bulletin of Yerevan University, 2017)
In the country economic growth is characterized as not qualitative, and the structure of the economy needs to be improved. In strategic sectors of the real sector of economy investments were not effectively allocated and did not contribute to economic development. In the sectors, sensitive to economic growth, an efficient allocation of investment can promote high-quality economic growth and development. Sectorial estimates of the elasticity of economic growth show that in the post-crisis period, the agricultural and industrial sectors showed considerable resilience and flexibility.